2014
DOI: 10.1007/s11103-014-0180-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional coordination between leaf cell differentiation and chloroplast development established by TCP20 and the subgroup Ib bHLH transcription factors

Abstract: The establishment of the photosynthetic apparatus during chloroplast development creates a high demand for iron as a redox metal. However, iron in too high quantities becomes toxic to the plant, thus plants have evolved a complex network of iron uptake and regulation mechanisms. Here, we examined whether four of the subgroup Ib basic helix-loop-helix transcription factors (bHLH38, bHLH39, bHLH100, bHLH101), previously implicated in iron homeostasis in roots, also play a role in regulating iron metabolism in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 69 publications
2
35
0
1
Order By: Relevance
“…To exert its function, FIT can form heterodimers with one of the four subgroup Ib bHLH proteins bHLH038, bHLH039, bHLH100, or bHLH101 [27,28] (Figure 1). The genes encoding these bHLH proteins are induced by Fe deficiency; however, unlike FIT, they are also strongly expressed in leaves, where they have Fe-deficiency-and leaf-development-related functions [30][31][32]. Analyses of overexpressing lines have shown that FIT collaborates with at least bHLH038 and bHLH039 to upregulate Fe-uptake genes [28].…”
Section: Strategy I Fe Acquisitionmentioning
confidence: 99%
“…To exert its function, FIT can form heterodimers with one of the four subgroup Ib bHLH proteins bHLH038, bHLH039, bHLH100, or bHLH101 [27,28] (Figure 1). The genes encoding these bHLH proteins are induced by Fe deficiency; however, unlike FIT, they are also strongly expressed in leaves, where they have Fe-deficiency-and leaf-development-related functions [30][31][32]. Analyses of overexpressing lines have shown that FIT collaborates with at least bHLH038 and bHLH039 to upregulate Fe-uptake genes [28].…”
Section: Strategy I Fe Acquisitionmentioning
confidence: 99%
“…3B). BHLH038 and BHLH100 have previously been shown to be induced when proliferating leaf cells stop dividing and start to expand (Andriankaja et al, 2012(Andriankaja et al, , 2014. These observations at the transcriptome level confirm the developmental shift in da1-1, bb/eod1-2, and da1-1_bb/eod1-2 compared with Col-0, showing that despite their larger size, leaves of the single mutants and especially da1-1_bb/eod1-2 were still in a younger developmental stage than those of Col-0.…”
Section: R358kmentioning
confidence: 99%
“…Genes promoting cell division in leaves, such as AN3 and ANT (Horiguchi et al, 2005;Mizukami and Fischer, 2000) and the mitotic marker CYCB1-1, which is highly expressed in proliferating leaves (Donnelly et al, 1999), were expressed more highly in da1-1, bb/eod1-2, and da1-1_bb/eod1-2 than in Col-0. Genes that are up-regulated during this transition, such as the negative regulator of cell division, KRP1, and two iron deficiency-responsive BHLH transcription factor genes, BHLH038 and BHLH100, that are linked to the sink/source transition in leaves (Andriankaja et al, 2012(Andriankaja et al, , 2014, were less expressed in these mutants. In a complementary fashion, 24 h after artificial induction of untagged DA1 and BB expression, downstream transcriptional responses related to the transition from cell proliferation to cell expansion, such as the up-regulation of BHLH038, BHLH039, BHLH100, and BHLH101 (Andriankaja et al, 2012(Andriankaja et al, , 2014, were observed.…”
Section: Da1 and Bb Restrict Leaf Growth Through Converging And Indepmentioning
confidence: 99%
See 1 more Smart Citation
“…While a post-embryonic function has been described for bHLH63, also known as CRYPTOCHROME-INTERACTING bHLH1 (CIB1; Liu et al, 2008) and bHLH100 (Andriankaja et al, 2014;Sivitz et al, 2012;Wang et al, 2007), no embryonic function has been reported for any of these genes. To determine whether these four bHLH genes are involved in S>E transformation, we first studied their embryonic expression domains in detail.…”
Section: Auxin-dependent Expression Of Bhlh Genesmentioning
confidence: 99%